2020
DOI: 10.1002/ajh.25837
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive lymphoma subtype is a risk factor for venous thrombosis. Development of lymphoma ‐ specific venous thrombosis prediction models

Abstract: Venous thromboembolic events (VTE) are a frequent complication of lymphoma. We conducted a retrospective analysis to compare VTE risk in diffuse large B‐cell lymphoma (DLBCL) and follicular lymphoma (FL). Subjects were randomly assigned to training and validation sets to identify risk factors of VTE and evaluate risk model performance, including the Khorana score. A group of 790 patients were diagnosed from 2002 to 2014 (DLBCL = 542, FL = 248). Median follow‐ up was 49 months. We observed 106 VTE, with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 25 publications
0
23
0
2
Order By: Relevance
“…Patients with lymphoma are at high risk for VTE; more while having active disease and on chemotherapy. 2123 In our study, at least half of lymphoma patients had the VTE while ambulatory around the time of VTE diagnosis. Obviously, none of such patients were on VTE prophylaxis.…”
Section: Discussionmentioning
confidence: 69%
“…Patients with lymphoma are at high risk for VTE; more while having active disease and on chemotherapy. 2123 In our study, at least half of lymphoma patients had the VTE while ambulatory around the time of VTE diagnosis. Obviously, none of such patients were on VTE prophylaxis.…”
Section: Discussionmentioning
confidence: 69%
“…(12) -7,7%. Veći broj naučnih radova navodi signifikantno veću učestalost VTE kod bolesnika sa agresivnim limfomima u odnosu na bolesnike sa indolentnim limfomima, uz variranje incidencije (12)(13)(14)(15)(16).…”
Section: Epidemiologijaunclassified
“…Iako se KS pokazao kad uslovno adekvatan alat za identifikaciju visokorizičnih pacijenata sa kancerom koji bi imali benefit od primene tromboprofilakse (19,48), performanse skora se nisu pokazale u potpunosti zadovoljavajućim kod specifične grupe pacijenata obolelih od limfoma (49). Takođe, pojedini podtipovi NHL, kao što su PMBCL, PNCSL i DBKL, karakteriše veća učestalost trombotičkih komplikacija u odnosu na indolentne limfome (5,6,16). Značajan problem KS je i niska senzitivnost koja se ogleda u činjenici da se većina VTE događaja kod pacijenata sa malignitetom zapravo događa izvan grupe visokog rizika (KS >3) (50).…”
Section: Epidemiologijaunclassified
“…In the study byAntic et al,(18) the rates of VTE development among lymphoma patients were 5.3% in the derivation cohort and 5.8% in the validation cohort. In a recently published article(19) focusing on DLBCL and follicular lymphoma, the reported rate of VTE development was 13.4%. These observed variations in the VTE rate in lymphoma patients are notable and may have several causes, including focusing on distinctive types of lymphoma, study methodology (e.g., retrospective vs. prospective), and publication time (more recent studies have been dedicated to CAT).…”
mentioning
confidence: 99%
“…(36)In our cohort, patients with aggressive lymphoma had a higher rate of VTE development (11.8%) than did patients with indolent lymphoma (5.8%) and HL (8.4%). Aggressive histology is predisposed to complicate the clinical course of lymphoma due to VTE (13,14,19,33,35,37). However, one large study by San lippo et al(38) concluded that the VTE risk for DLBCL is lowered after adjusting for additional risk factors.…”
mentioning
confidence: 99%